THE STRATEGIES OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN SHAPING STUDENTS RELIGIOUS CHARACTER AT SD NEGERI 168 REJANG LEBONG - Jerri Sundari; Feni Karya Utami; M. Azimmullah Ilyas; Aida Rahmi Nasution; Mirzon Daheri (Program Studi Pendidikan Agama Islam, 2026)
Development character religious at the level school base own role important in form moral and religious behavior participant Educate . Islamic Religious Education (PAI) teachers are required to For implementing appropriate strategies to encourage internalization Islamic values in general effective . Research This aim For analyzing the strategies of Islamic Religious Education teachers in form character religiosity students at SD Negeri 168 Rejang Lebong . The method used is descriptive qualitative through interviews , observations , and documentation . Research results show that Islamic religious education teachers implement various strategies, including role models , habituation activity religious, integration cross- Islamic values eye lessons and work The same with parents . The strategy give impact positive in behavior religious student in life everyday . However Still there is constraint like lack of consistency home habits and influences​ environment outside school . Therefore that , synergy between schools , families and communities are very necessary For optimize education character religious.